The new readout system for the ALICE Zero Degree Calorimeter in LHC Run 3 - De Remigis Paolo; Cortese Pietro; Cotto Giorgio; De Marco Nora; Lombardo Luca; Puggioni Carlo; Sitta Mario; Zugravel Stefan Cristi (EPJ Web of Conferences, 2023)
The Zero Degree Calorimeter (ZDC) was designed to provide the event geometry and luminosity measurements in heavy-ion operation. In order to exploit the potential offered by the LHC’s increased luminosity in Run 3, the ZDC upgraded its readout system to acquire all collisions in self triggered mode without dead time. The purpose of the upgrade was to enable the detector to cope with the increased event rate while preserving its time and charge resolution performance. The ZDC operating conditions in Run 3 Pb – Pb collisions are extremely challenging due to the presence of electromagnetic dissociation processes (EMD). For example when running in self-triggered mode the ZDC system will need to sustain a readout rate of ∼2.5 MHz for the channels of the most exposed calorimeters compared to the foreseen hadronic rate of 50 kHz sustained by the other detectors. The previous electronics, based on Charge-to-digital converters (QDCs), with a fixed dead time of ∼ 10 μμs, and on readout through VME bus, could not cope with such a high rate. Moreover, a crucial aspect of the ZDC operation in Run 3 is acquiring the events with a reduced bunch spacing of 50 ns (lower than the length of the signal of ∼ 60 ns) in the presence of high signal dynamics (from a single neutron to ∼ 60 neutrons). The new acquisition chain is based on a 12 bit digitizer with a sampling rate of about 1 GS/s, assembled on an FPGA Mezzanine Card. The signals produced by the ZDC channels are digitized, and samples are processed through an FPGA to extract information such as timing, baseline average estimation and luminosity. The architecture of the new readout system, the auto trigger strategy, the firmware organization and the ZDC performance during 2022 Pb–Pb collisions are presented.